The Ghent system of social insurance: a model for Australia?. (3rd July 2021) - Lansbury, Russell D.
ABSTRACT: This commentary examines the 'Ghent system' of social insurance, which has been adopted in most countries in the Nordic region of Europe, and analyses its suitability for Australia. Of particular concern is whether adopting the Ghent system could assist trade unions in Australia to gain greater membership coverage of the workforce, given that it is widely credited as having played this role in the Nordic countries. The paper begins with a brief description of the Ghent system, its origins in Belgium in the early twentieth century, and variations of how the system has been applied in some of the Nordic countries. Finally, there is a discussion of what Australian unions can learn from the experiences of the Ghent system in the Nordic countries and under what circumstances it might be applicable to Australia.